Seasonal Cycling of Mercury in the Antarctic Sea Ice Environment - Nerentorp, Michelle (2014)
Mercury is a globally distributed contaminant that exists in the atmosphere as a stable monoatomic gas. Having almost a year’s residence time in the air allows it to reach remote polar regions. Deposited airborne mercury can be transformed in the environment to the organic and bio-accumulating compound methyl mercury. Methyl mercury is neurotoxic and affects land living and marine animals all over the world. Springtime atmospheric mercury depletion events, first discovered in 1995 in the Arctic, occur when the return of sunlight induces the formation of halogen radicals that oxidize tropospheric elemental mercury. These spring events occurring in polar regions increase the net deposition of mercury into polar marine ecosystems. Some studies have been performed on the fate of mercury deposited onto snowpack but the transportation and transformation of mercury through and within snow and sea ice are still not fully understood.This thesis is based on data from three oceanographic expeditions to Antarctica (winter, spring and summer). Here unique seasonal data are presented for mercury species in air and elemental and total mercury concentrations in snow, sea ice, sea water and brine. Results presented in this thesis show that atmospheric mercury depletion events also occur over sea ice areas in the middle of the dark winter period. The dark depletions lead to an increased net deposition of mercury onto surface snow. Results also show that when approaching warmer and more sunlit seasons, the reduction of deposited oxidized mercury increases and this leads to more re-emission of elemental mercury back into the atmosphere. Melting sea ice also increases the leaching of mercury in snow and ice via run-off and via brine channels to the sea water under the ice floes. In this thesis it is also shown that the amount of solar radiation and overlaying snowpack affect the concentrations of elemental mercury in sea ice. This indicates that photo-reduction of mercury occurs within sea ice and may be important for mercury ...